On a mixed problem for systems of definite quasilinear partial differential equations with deviating argument - Marynetz, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
For a mixed problem for a system of definite quasilinear pseudoparabolic equations with deviating argument, we prove a theorem on differential inequalities and existence of a unique regular solution and a comparison theorem and give sufficient conditions of existence of solutions with constant sign.